2002
DOI: 10.1136/heart.88.6.640
|View full text |Cite
|
Sign up to set email alerts
|

Variable seasonal peaks for different types of aortic dissection?

Abstract: Seasonal differences in the manifestation of cardiac death caused by arrhythmia, heart failure or acute myocardial infarction, with peaks during winter months, have been reported.1 Circadian patterns have also been shown for aortic dissection.2 A recent large population based study failed to find convincing statistical evidence of seasonal variability for ruptured aneurysms and dissections of the abdominal aorta. 3 An analysis of 85 patients with non-traumatic rupture of the thoracic aorta found a higher occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 5 publications
4
10
2
Order By: Relevance
“…Studies to date that have examined the association between season and incidence of SA-AoD have yielded mixed results. A statistically significant seasonal variation with a peak in winter was observed by two European case series (France, n ¼ 206, p ¼ 0.018; Switzerland, n ¼ 282, p ¼ 0.011) (Benouaich et al, 2010;Kobza et al, 2002). In contrast, a seasonal variation in incidence was not observed among 570 patients with SA-AoD enrolled in the International Registry of Acute Aortic Dissection (IRAD) between 1996 and 2000 (p ¼ 0.31) (Mehta et al, 2002).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Studies to date that have examined the association between season and incidence of SA-AoD have yielded mixed results. A statistically significant seasonal variation with a peak in winter was observed by two European case series (France, n ¼ 206, p ¼ 0.018; Switzerland, n ¼ 282, p ¼ 0.011) (Benouaich et al, 2010;Kobza et al, 2002). In contrast, a seasonal variation in incidence was not observed among 570 patients with SA-AoD enrolled in the International Registry of Acute Aortic Dissection (IRAD) between 1996 and 2000 (p ¼ 0.31) (Mehta et al, 2002).…”
Section: Discussioncontrasting
confidence: 59%
“…Other studies of aortic dissection and season have reported statistical results as a pooled group, often because of small numbers or convenience (Lasica et al, 2006;Manfredini et al, 2008;Matsuo, 1998;Sumiyoshi et al, 2002;Upshur et al, 2000). However, these studies are difficult to interpret since it is not wellestablished whether all types of aortic dissection follow a similar seasonal distribution (Kobza et al, 2002;Mehta et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…According to a series of studies, fall and winter months represent a high-risk temporal frame for occurrence of aortic rupture or dissection, [56][57][58][59][60][61][62][63][64][65][66][67][68][69] although there is also evidence of no seasonality 70,71 (Table 2).…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…The median length of hospitalization (survival to discharge) was significantly longer in type A than in type B (type A: 28 (20-40) vs type B: 22 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) days; p<0.001) ( Table 1). Compared with open surgery, the hospitalization duration was shorter in patients who underwent TEVAR for type B (TEVAR: 22 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) vs open surgery: 42 (30-62) days) ( Table 3); however, no marked difference was found in those with type A (TEVAR: 31 vs open surgery: 28 (20-41) days). The medical costs of the patients who were discharged alive were more than five times higher in type A patients than that in type B patients (type A: 6.26 vs type B: 1.18 million Japanese yen) ( Table 1).…”
Section: Length Of Hospital Stay and Medical Costmentioning
confidence: 99%